De-industrialization or re-industrialization? On the future of the Eastern German economy - Klaus-Dieter Schmidt; Petra Naujoks (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
The paper is intended to explore the prospective direction of structural adjustment in eastern Germany in the light of recent developments. The authors do argue that the Mezzogiorno-picture, a completely de-industrialized region between the Elbe- and the Oder-river, is not convincing. In the long-run, say in two decades, eastern Germany has good opportunities to become the most modern and competitive industrial basis in central Europe. In the medium-run, however, a dualization is likely - an industry with a rather new, highly capital-intensive segment and a subsidized old one. Consequently, there will emerge fast growing regions within Eastern Germany, so-called productivity islands, and regions with high chronical unemployment. This will be the unavoidable price for a very rapid equalization of real wages between east and west.
Keywords: 330; Wirtschaftliche Anpassung; Wirtschaftsprognose; Neue Bundesländer